109k views
1 vote
Answer parts a through E for the function shown below

Answer parts a through E for the function shown below-example-1
User Oluckyman
by
5.0k points

1 Answer

6 votes

Solution

We are given the function


f(x)=x^3+4x^2-x-4

First, Let us do the simplification or factorization


\begin{gathered} f(x)=x^2(x+4)-1(x+4) \\ f(x)=(x^2-1)(x+4) \\ f(x)=(x-1)(x+1)(x+4) \end{gathered}

(a).

The coefficient of x^3 is positive

(b).

So basically, we set f(x) = 0 to get the x - intercepts


\begin{gathered} f(x)=(x-1)(x+1)(x+4) \\ (x-1)(x+1)(x+4)=0 \\ x=1,-1,-4 \end{gathered}

The x - intercepts are


x=1, -1, -4

The graph of f(x) is also given below

Answer parts a through E for the function shown below-example-1
Answer parts a through E for the function shown below-example-2
Answer parts a through E for the function shown below-example-3
User Gates
by
5.6k points